2012
DOI: 10.1108/01409171211238253
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management: the case of NGOs in Palestine

Abstract: Purpose -The purpose of this paper is to explore whether non-governmental organizations' (NGOs') managers think and use strategy in their daily operations, to assess the impact of its applications on the performance of NGOs and to test the validity of the "dynamic model of strategic management" originally used for small and medium-sized enterprises (SMEs) in the Gaza Strip, Palestine. Design/methodology/approach -This empirical study is concerned with NGOs' managers located in the Gaza Strip in Palestine. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…When employees deliver the interventions to the beneficiaries with a high level of performance, the organization meets the beneficiary's satisfaction. Altayeb and Alhasanat () establish that employees' engagement, training, and empowerment are obligatory for successful TQM implementation, while Analoui and Samour () find that strategic HR management is the most important factor to improve the strategic performance particularly in nongovernmental organizations due to the diversity of actors involved, for example, paid staff, volunteers and community activists, and others, whose coordination requires more than standard HR processes (Hack‐Polay & Igwe, ). Ridder, Piening, and Baluch () confirm the rising importance of HR management in a nonprofit setting, particularly as a result of funding cutbacks, and the need to serve multiple stakeholders while facing a scarcity of resources.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…When employees deliver the interventions to the beneficiaries with a high level of performance, the organization meets the beneficiary's satisfaction. Altayeb and Alhasanat () establish that employees' engagement, training, and empowerment are obligatory for successful TQM implementation, while Analoui and Samour () find that strategic HR management is the most important factor to improve the strategic performance particularly in nongovernmental organizations due to the diversity of actors involved, for example, paid staff, volunteers and community activists, and others, whose coordination requires more than standard HR processes (Hack‐Polay & Igwe, ). Ridder, Piening, and Baluch () confirm the rising importance of HR management in a nonprofit setting, particularly as a result of funding cutbacks, and the need to serve multiple stakeholders while facing a scarcity of resources.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Whereas, Non-Governmental Organization (NGO) study results in Palestine indicated some positive results in SM practice. Analoui and Samour (2012) study revealed that the utmost NGOs in Palestine was using SM tools, and they perceived that the practice of SM is a vital tool for the quality of services delivery enhancement. Their results came in line with Al Shobaki& Amuna and Naser (2017) results, which indicated that there are some SM tools mainly SP and operational planning are practiced in the "United Nations Relief and Works Agency for Palestine Refugees in the Near East" (UNRWA), and it has appositive results on their performance.…”
Section: Sm Applications In Some Middle East Countriesmentioning
confidence: 99%
“…Collective action theory has the intention to identify which stakeholder group requires most attention from the connective company. The central idea of the collective action theory is that the success of a corporation links tight to how well the central corporation succeeds to communicate with its actors (Blood, 2004;Arenas et al, 2009;Analoui and Samour, 2012).…”
Section: The Conceptual Frameworkmentioning
confidence: 99%